Research on the Innovative Path of Cultural and Creative Transformation of Tibetan Thangka Intangible Cultural Heritage - Wang, Lulu; Da, Wazhasang; Mohamed, Fauzi Naeim (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2025)
This study examines the innovative integration of Tibetan Thangka, a 1,300-year-old painting tradition and national intangible cultural heritage, with contemporary cultural and creative industries. The research aims to identify effective strategies for preserving Thangka's cultural essence while enhancing its market viability and social relevance in the digital age. Using a mixed-methods approach combining literature analysis, case studies of successful cultural transformations, and comparative evaluation of existing Thangka initiatives, this study develops a